Liste commentee des Gasteropodes testaces marins recueillis dans les depots littoraux actuels du Golfe de Tunis - FEKIH, Mohamed; GOUGEROT, Louis (INSTM Bulletin : Marine and Freshwater Sciences, 1974)
The list, comprising 432 species of Gastropod sea-shells, which were collected from 1964 to 1972 on the shores of the Tunis Gulf, is the most complete since that of Pallary (1914), which only comprised 224 species. This difference principally comes from the collection of very small species which were neglected by previous authors. Taxonomic comments are given for some of them. Two new species and one new sub-species are described and pictured at the end of this paper..